Leveraging federalism for flexible and robust management of social‐ecological systems. Issue 2 (16th February 2023) - Sims, Charles; Armsworth, Paul R.; Blackwood, Julie; Fitzpatrick, Ben; Kling, David M.; Lenhart, Suzanne; Neubert, Michael; Papeş, Monica; Sanchirico, James; Shea, Katriona; Springborn, Michael
Abstract: Managing social‐ecological systems (SES) requires balancing the need to tailor actions to local heterogeneity and the need to work over large areas to accommodate the extent of SES. This balance is particularly challenging for policy since the level of government where the policy is being developed determines the extent and resolution of action. We make the case for a new research agenda focused on ecological federalism that seeks to address this challenge by capitalizing on the flexibility afforded by a federalist system of governance. Ecological federalism synthesizes the environmental federalism literature from law and economics with relevant ecological and biological literature to address a fundamental question: What aspects of SES should be managed by federal governments and which should be allocated to decentralized state governments? This new research agenda considers the bio‐geo‐physical processes that characterize state‐federal management tradeoffs for biodiversity conservation, resource management, infectious disease prevention, and invasive species control. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.